ANALISIS IMPLEMENTASI PP NOMOR 71 TAHUN 2010 TENTANG STANDAR AKUNTANSI PEMERINTAHAN (SAP) BERBASIS AKRUAL PADA PEMERINTAH KABUPATEN SEKADAU - B2092172006, ERDY MUSHARDY (MAKSI, 2020)
This research attemps to better understand and analyse teh implementation of government regulation no. 71 of 2010 on accrual-based government accounting standards (SAP) on the government of Sekadau Regency.This research was qualitative in nature. The data was collected thorugh interview, observation, and documentation. The technique was carried out interactively by interviewing the participants. Menwhile, the non-interactive technique was performed thourgh a documentation study by analysing contents of the documents related to financial reports.Data indicated that the implementation of government regulation no. 71 of 2010 on accrual-based government accounting standards (SAP) on the government of Sekadau Regency was completely carried out. However, several accrual transactions were not recorded on the government of Sekadau Regency balance sheet in 2017 such as liabilities for workload-based addtional income expenditures as much as Rp 8.211.418.115,50 and salaries payable for non-permanent employees as much as Rp 1.636.976.124,00. In addtion, BPK-RI branch West Kalimantan Province made some correction towards Account Receivable (A/R) of PAD as much as Rp 331.702.191,44. A correction was also made towards shorty term liabilities as much Rp 221.848.388,00 because this number should be recorded in long tern liabilities account.Government regulation no. 71 of 2010 on accrual-based government accounting standards (SAP) could provide a complete picture of the government?s financial position. Therefore, it will facilitate the government to control a financial management and help them make a decision to determine future?s plans. Key Word : Implementation, Accounting Standard , SAP No. 71 of 2010, Accrual BasedDAFTAR PUSTAKAAnngraeni. A (2016) Analisis Implementasi PP. No 71 Tahun 2010 dan PMK 272/PMK.05/2014 Dalam Proses Penyusunan Laporan Keuangan di Universitas Tanjungpura Asmiati, S., & Walandouw, S. K. (2015, Maret). Evaluasi Penerapan Pernyataan Standar Akuntansi Pemerintahan Tentang Penyajian Laporan Realisasi Anggaran Pemerintah Kabupaten Minahasa Utara. Jurnal EMBA, 3(1), 418-425. Bastian, I. (2006). Akuntansi Sektor Publik: Suatu Pengantar. Jakarta: Erlangga.Bastian, I. (2006). Sistem Akuntansi Sektor Publik: Edisi Dua. Jakarta: Salemba Empat. Dico, D., Tinangon, J. J., & Pusung, R. J. (2014, Juni). Analisis Pengelolaan dan Pelaporan Keuangan Pada Satuan Kerja Bidang Keuangan Polda Sulawesi Utara. Jurnal EMBA, 2(2), 1130-1140. Gunawan, I. (2013). Metode Penelitian Kualitatif. Jakarta: Bumi Aksara. Halim, A. (2007). Akuntansi Sektor Publik Akuntansi Keuangan Daerah. Edisi Tiga. Jakarta: Salemba Empat. Harun. (2009). Reformasi Akuntansi dan Manajemen Sektor Publik di Indonesia. Jakarta: Salemba Empat. Jogiyanto. (2007). Metodologi Penelitian Bisnis: Salah Kaprah dan Pengalaman Pengalaman. Yogyakarta: BPFE. Kieso, D. E., Weygandt, J. J., & Warfield, T. D. (2002). Intermediate Accounting, Tenth Edition. (E. Salim, Penerj.) Jakarta: Erlangga. Kementerian Keuangan Republik Indonesia. (2014). Modul Gambaran Umum Akuntansi Berbasis Akrual. Jakarta: Kementerian Keuangan RI. Komite Standar Akuntansi Pemerintahan. (2012, Agustus 8). Buletin Teknis dan Interpretasi PSAP . Dipetik September 16, 2015, dari KSAP Website: http://www.ksap.orgLangelo, F., Saerang, D. P., & Alexander, S. W. (2015, Maret). Analisis Penerapan Standar Akuntansi Pemerintahan Berbasis Akrual dalam Penyajian Laporan Keuangan Pada Pemerintah Kota Bitung. Jurnal EMBA, 3(1), 1-8. Niu, F. A., Karamoy, H., & Tangkuman, S. (2014, Desember). Analisis PenerapanNo. 71 Tahun 2010 Dalam Penyajian Laporan Keuangan Dinas Pendapatan Pengelolaan Keuangan dan Aset Daerah Kota Kotamobagu. Jurnal EMBA, 2(4), 714-722. Ningtyas, F. N., Poputra, A. T., & Lambey, R. (2015, Maret). Evaluasi Penerapan Peraturan Pemerintah Nomor 71 Tahun 2010 Pada Dinas Energi dan Sumber Daya Mineral Provinsi Sulawesi Utara. Jurnal EMBA, 3(1), 455-462. Pajouw, R. V., Poputra, A. T., & Afandi, D. (2015, Maret). Analisis Pencatatan dan Pelaporan Keuangan Pada Unit Pelaksana Teknis Dinas di Pemerintah Provinsi Sulawesi Utara. Jurnal EMBA, 3(1), 769-777. Perdhana Iqbal. (2017) Analisis Penerapan Standar Akuntansi Pemerintahan (SAP) Berbasis Akrual pada Pemerintah Kabupaten Mempawah. Republik Indonesia. (2005). Peraturan Pemerintah Nomor 24 Tahun 2005 tentang Standar Akuntansi Pemerintahan. Lembaran Negara RI Tahun 2005 Nomor 49. Jakarta: Kementerian Hukum dan HAM RI. Republik Indonesia. (2010). Peraturan Pemerintah Nomor 71 Tahun 2010 tentang Standar Akuntansi Pemerintahan. Lembaran Negara RI Tahun 2010 Nomor 123. Jakarta: Sekretariat Negara. Republik Indonesia. (2010). Peraturan Menteri Dalam Negeri Nomor 13 Tahun 2006 tentang Pedoman Pengelolaan Keuangan Daerah. Soputan, C., Sondakh, J. J., & Tangkuman, S. (2015, Maret). Penyajian Laporan Keuangan Pemerintah Berdasarkan PP Nomor 71 Tahun 2010 Tentang Standar Akuntansi Pemerintah di Provinsi Sulawesi Utara. Jurnal EMBA, 3(1), 592-600. Sampel, I. F., Kalangi, L., & Runtu, T. (2015, Maret). Analisis Kesiapan Pemerintah Kota Manado Dalam Penerapan Peraturan Pemerintah Nomor 71 Tahun 2010 Mengenai Standar Akuntansi Berbasis Akrual. Jurnal EMBA, 3(1), 621-630.